Alterations in Semen Quality and Immune‐Related Factors in Men with Infertility who Recovered from COVID‐19 - Ying Zhang; Feiyin Zhu; Zhe Zhang; Jing Wang; Tianyi Liao; Yu Xi; Defeng Liu; Haitao Zhang; Haocheng Lin; Jiaming Mao; Wenhao Tang; Lianming Zhao; et al. (MedComm)
ABSTRACT The emergence of coronavirus disease 2019 (COVID‐19) has triggered research into its impact on male reproductive health. However, studies exploring the effects of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) on semen quality in infertile men remain limited. Herein, we enrolled 781 male infertile patients who recovered from COVID‐19 and analyzed their semen and blood samples collected at different time points. We found that SARS‐CoV‐2 RNA was undetectable in semen samples. Compared with pre‐COVID‐19 status, total sperm count, sperm concentration, vitality, motility, and percentage of sperm cells with normal morphology decreased significantly in the first month post‐COVID‐19. However, these alterations were reversed in the third month. Furthermore, seminal plasma samples exhibited reduced proinflammatory cytokine levels and notable changes in amino acid, nucleic acid, and carbohydrate metabolism by the third month compared with those in the first month. By contrast, no significant alterations in reproductive hormone levels were found. Vitality, progressive motility, and total motility negatively correlated with body temperature when it was above 38°C. In conclusion, semen quality initially decreases post‐COVID‐19 but reverses after approximately 3 months, with a decline related to inflammatory and fever. These findings may provide guidance to infertile male patients who need assisted reproductive technology.